"Art on Behalf": Introducing an accessible art therapy approach used in palliative care. (February 2020) - Ganzon, Claire; O'Callaghan, Clare; Dwyer, Justin
Highlights: Art on Behalf allows engagement in art therapy without expectation of making art. Art on Behalf accommodates patients dealing with fatigue and other effects of serious illness. Psychotherapeutic processes are evident in case descriptions of the Art on Behalf art therapy approach. Abstract: There are multiple barriers to art therapy engagement in the palliative care setting, including treatment fatigue, the intrusive nature of the inpatient hospital environment, and the wide variation in patient health status. This paper describes a response to these challenges with Art on Behalf, an art therapy approach in which the art therapist creates an artwork on behalf of the patient. The patient conceptualizes the image while the art therapist produces the painting. Art-making is not obligatory in this process, and the patient may feel inspired to create art at a later time. Case study methodology is used to describe three cases that illustrate the psychotherapeutic aspects of the Art on Behalf approach that offered meaningful art therapy engagement within the many restrictions of the palliative care environment.